STUDI EVALUASI STRATEGI PENINGKATAN PENERIMAAN PENDAPATAN DAERAH MELALUI PROGRAM PENINGKATAN KAPASITAS DAN KINERJA PADA BADAN PENDAPATAN DAERAH PROVINSI SILAWESI SELATAN - Ali Taufiq; Muhammad Idrus Taba; Muhammad Sobarsyah (Hasanuddin Journal of Applied Business and Entrepreneurship, 2019)
The purpose of this research is to analyze the evaluation process of the implementation of SKPD capacity and performance improvement program strategy with SWOT analysis. This research uses quantitative methods because this research is presented with words or verbs from people and observable behaviors. The reason for choosing a qualitative approach is because it relates to the concept of title and problem formulation on the evaluation study of regional income revenues improvement strategy through capacity building and performance program at Regional Revenue Board of South Sulawesi Province. Based on the results of the evaluation process analysis of the implementation of the capacity and performance improvement program strategy, the strategy undertaken by the Regional Income Board of South Sulawesi Province in an effort to increase the revenue of the region through capacity and performance improvement program is intensification strategy which is done through the improvement of operational power capability in the field, take advantage of roles and cooperation with agencies in the management and supervision of revenue revenues and assess the shortcomings and maximize the local financial management system.